Research on the Integration of Intangible Cultural Heritage into the Aesthetic Education Program of Higher Vocational Universities - Huang, Ting; Ariunaa Sh (International Journal of Social Sciences and Public Administration, 2024)
This study focuses on exploring how local intangible cultural heritage (ICH) can be effectively integrated into the higher vocational aesthetic education curriculum in the context of the integration of industry and education with a view to enhancing the comprehensive quality and vocational competence of the students, and it adopts a methodology that includes literature review, case study analysis, and teaching experiments in order to comprehensively examine the ways in which ICH culture can be integrated into education and its effects. The study found that the integration of intangible cultural heritage culture significantly enhanced students’ sense of cultural identity and innovation ability, and the learning outcomes were reflected in the improvement of professional skills and aesthetic quality. The integration of intangible cultural heritage culture education is an important direction for the reform of higher vocational aesthetic education curriculum, and curriculum design, teacher training and practice platform construction should be strengthened in the future teaching practice in order to realize the comprehensive and lifelong development of education.